Low Risk of Injuries in Young Adolescents Participating in Top-Level Karate Competition. (February 2016) - Arriaza, Rafael; Inman, David; Arriaza, Alvaro; Saavedra, Miguel A.
Background: Prospective studies on injuries in martial arts competition are scarce, especially those involving young practitioners, but the upsurge of children and adolescents taking part in organized training and competition in these sports requires clarification of the injury risk that they represent for youths. Hypothesis: Top-level karate competition for young adolescents (cadets, or 14- to 15-year-olds) has a low injury rate and can be safely promoted. Study Design: Descriptive epidemiological study. Methods: Prospective recording of the injuries resulting from all bouts in 3 consecutive World Karate Championships (2009, 2011, and 2013) for cadets was performed. Data were collected prospectively in situ with checklists that described competitor sex, bout category, and weight as well as injured area, diagnosis, mechanism of injury, severity, and treatment. Results: A total of 1020 bouts were reviewed, 671 in the male category and 349 in the female category. A total of 61 injuries were recorded. Of those, only 3 were time-loss injuries. During the 2009 and 2011 championships, there was 1 injury per 25.6 fights, while during the 2013 championship the number of injuries increased, with 1 injury per 10 fights ( P = .003). There was no statistical difference in the total injury rate between the male and female categories ( P = .71), with an odds ratio of 1.16 (95% CI, 0.52-2.55). Conclusion: The injury rate for cadet top-level karate competition found in this prospective study is much lower than the rates previously published for karate or other martial arts competitions, but there seems to be a marked increase as more championships are held, which is a matter of concern.